Proceedings of the 1st International Conference on Innovation in Education (ICoIE 2018) 2019
DOI: 10.2991/icoie-18.2019.52
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Effort in Improving Historical Writing Skill by Presenting Historian as Resources Person on Historical Learning

Abstract: Educational world has long demanded History teacher to abandon teacher-centered learning approach (expository), but the fact says that most of the teachers are reluctant to abandon the conventional approach. Therefore, the use of lecture method often dominates the delivery of historical learning. It is not surprising that History is suspected as a boring and uninteresting subject. The condition encourages researcher to observe History teacher at public senior high school in Bandung who use historians as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results of observations made by Yulifar (2019) revealed that history teaching in high school used a method approach and took place according to a pattern with a teacher providing information, and students listening and writing. In addition, there were question-and-answer sessions and assignments (Yulifar, 2019). The normative type of teacher also still applied teacher-centered learning.…”
Section: Discussionmentioning
confidence: 99%
“…The results of observations made by Yulifar (2019) revealed that history teaching in high school used a method approach and took place according to a pattern with a teacher providing information, and students listening and writing. In addition, there were question-and-answer sessions and assignments (Yulifar, 2019). The normative type of teacher also still applied teacher-centered learning.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the teacher is still conventional and does not arouse creative imaginative students. Conventional history learning will cause serious problems, considering that students are increasingly critical in the midst of developing information [2]. Learning methods such as discussion and question and answer sharpens students critical thinking but does not hone students creativity.…”
Section: Proceedings Of the 6th International Conference On Education And Social Sciences (Icess 2021)mentioning
confidence: 99%
“…Even some history teachers revealed that learning history has not been attractive to students because of the lack of creativity in learning. However, according to [8] with creativity, learning objectives will be achieved optimally through fun ways that include three domains of knowledge, attitudes and skills. This is in line with the teacher's efforts in designing and implementing history learning with a scientific approach so that classical problems in history learning can be resolved, expository becomes student-centred, the phenomenon of boredom becomes fun learning.…”
Section: Introductionmentioning
confidence: 99%